Reimagining Marginalized Foods Global Processes, Local Places - Finnis, Elizabeth (University of Arizona Press, 2012)
This volume brings together ethnographically based anthropological analyses of shifting meanings and representations associated with the foods, ingredients, and cooking practices that of marginalized and/or indigenous cultures. Contributors are particularly interested in how these foods intersect with politics, nationhood and governance, identity, authenticity, and conservation.